ANALISIS KESIAPAN GURU PEMULA DALAM MENGAJARKAN KETERAMPILAN BERPIKIR KRITIS DAN KREATIF - Sarjana, Ketut; Lu'luilmaknun, Ulfa; Intan Kertiyani, Ni Made; Kurniawan, Eka (Mandalika Mathematics and Educations Journal, 2025)
This study aims to analyze the readiness of novice mathematics teachers in Mataram City to teach critical and creative thinking skills to junior high school students. A descriptive method was employed with a purposive sample of 23 novice teachers. The research instrument consisted of tests measuring teachers' understanding of critical and creative thinking concepts and their ability to formulate questions that foster these skills. The results indicate that most novice teachers have good readiness, with an average score of 77.23. However, readiness varies by teaching experience, where teachers with 0–1 year and over 5 years of experience show higher readiness than those with 1–3 and 3–5 years of experience. These findings highlight the necessity of continuous training and mentoring to sustain and improve novice teachers’ competence in teaching 21st-century skills. The study recommends the development of focused professional development programs aimed at enhancing teachers’ abilities to teach critical and creative thinking.